Epidural insertion height for ureteric reimplant surgery; does location matter?. Issue 10 (7th April 2016) - Sommerfield, David; Ramgolam, Anoop; Barker, Andrew; Bergesio, Ric; von Ungern‐Sternberg, Britta S
Summary: Background: Surgical correction of vesicoureteric reflux through ureteric reimplantation is a common, highly successful treatment. Postoperative pain can be severe and may relate to somatic wound pain from the lower abdominal incision or from visceral bladder spasm pain. Aim: To conduct a prospective quality improvement audit to compare four perioperative analgesic techniques. Methods: Observational data were collected on 217 patients following open ureteroneocystostomy over 5 days. The patients were split into four groups: (i) 'morphine' infusion; (ii) 'caudal'—single‐shot caudal; (iii) 'epidural'—epidural catheter inserted at T10‐L2 given a bolus, followed by an infusion of 0.125% bupivacaine with fentanyl 2 μg·ml −1 ; (iv) 'caudal catheter'—caudal placed epidural catheter was treated similar to the epidural catheter. Data regarding postoperative analgesic interventions were recorded. Intravesical pethidine was used for bladder spasm pain and i.v. morphine for wound pain. Results: Over the study period, the caudal catheter technique (mean interventions/patient = 1.8 ± 2.6) and the single‐shot caudal (6.1 ± 4) needed significantly less bladder spasm interventions than morphine (9.2 ± 4) and epidural (8.0 ± 4.4) patients. For wound pain, the caudal catheter (8.8 ± 3.3) and epidural groups (11.4 ± 3.2) needed significantly less interventions than morphine (16.1 ± 3) and caudal (15.3 ± 3.3) patients. Overall, caudal catheter patients on average required about half the number of pain interventions and were associated with less high nursing workload. Conclusions: Despite some limitations in data collection and study design, the caudal catheter technique was superior at reducing pain interventions, particularly bladder spasm interventions. Overall epidural analgesia was not superior to a single‐shot caudal followed by opioid infusion. The issue of bladder spasm may be similar to the phenomenon of sacral sparing in obstetric epidural anesthesia. Thus, regional techniques, such as caudal epidural, targeting a better balance between sacral and lumber nerves are required. Abstract :